E-Business and Telecommunications : 11th International Joint Conference, ICETE 2014, Vienna, Austria, August 28-30, 2014, Revised Selected Papers - Obaidat, Mohammad S.; Holzinger, Andreas; Filipe, Joaquim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 11th International Joint Conference on E-Business and Telecommunications, ICETE 2014, held in Vienna, Austria, in August 2014. ICETE is a joint international conference integrating four major areas of knowledge that are divided into six corresponding conferences: International Conference on Data Communication Networking, DCNET; International Conference on E-Business, ICE-B; International Conference on Optical Communication Systems, OPTICS; International Conference on Security and Cryptography, SECRYPT; International Conference on Wireless Information Systems, WINSYS; and International Conference on Signal Processing and Multimedia, SIGMAP. The 27 full papers presented were carefully reviewed and selected from 328 submissions. The papers cover the following key areas of e-business and telecommunications: data communication networking; e-business; optical communication systems; security and cryptography; signal processing and multimedia applications; wireless information networks and systems.
Data communication networking -- E-business -- Optical communication systems.-Security and cryptography -- Signal processing and multimedia applications.-Wireless information networks and systems.
Keywords: Computer Communication Networks; Computer security; Information storage and retrieva; Computer Communication Networks; Systems and Data Security; Information Systems Applications (incl. Internet).; Information Storage and Retrieval